Comparative legal analysis of international experience in corporate dispute resolution: institutional approaches and possibilities of adaptation to the legislation of Kazakhstan - Baikenzhina, Sh.T.; Ilyassova, G.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article is devoted to the comparative legal analysis of institutional approaches to corporate dispute resolution in leading foreign jurisdictions and the possibilities of their adaptation to the legislation of the Republic of Kazakhstan. The purpose of the study is to identify key elements through the prism of global legal practice that ensure the effectiveness of corporate dispute resolution – the availability of specialized courts, a well-developed system of arbitration and mediation, protection of minority shareholders’ rights and flexibility of procedures. To achieve this goal, analyzed the effectiveness of foreign approaches in terms of the speed of dispute resolution and transparency of procedures, and explored best practices and legal instruments potentially applicable in the legal field, considering the specifics of national legislation, judicial practice and institutional infrastructure. The scientific and practical significance of the work lies in the systematization of international experience and the definition of directions for the reform of national legislation. The methodological part uses comparative law, formal law and the method of legal modeling. As a result, institutional and procedural mechanisms have been identified to ensure the effectiveness of corporate dispute resolution in different legal systems, and the conditions for their possible integration into the Kazakh legal system have been analyzed. The work contributes to the development of legal institutions in corporate law and suggests ways to improve law enforcement practice in the Republic of Kazakhstan. The practical significance lies in the formulation of recommendations for participants in the corporate process and judicial authorities.